2019
DOI: 10.12968/jowc.2019.28.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of partial-thickness burns with a tulle-gras dressing and a hydrophilic polyurethane membrane: a comparative study

Abstract: Objective: The purpose of this revisited study was to compare the clinical efficacy and long-term scar evaluation of a hydrophilic polyurethane membrane (HPM), Omiderm (Omikron Scientific Ltd., Rehovot, Israel) and an antimicrobial tulle-gras dressing (TGD), Bactigras (Smith & Nephew) in the management of partial-thickness burns. Method: Patients with partial-thickness burns were enrolled in this prospective study. Burn areas were divided into two areas and both dressings were applied to each field at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Despite of the advance technology and researches, pathogenesis and antibiotic. 15 Resistance mechanisms, Enterobacter and P. aeruginosa were found to be MDR. All isolates, in our study were found to be imipenem and meropenem sensitive.…”
Section: Methodsmentioning
confidence: 99%
“…Despite of the advance technology and researches, pathogenesis and antibiotic. 15 Resistance mechanisms, Enterobacter and P. aeruginosa were found to be MDR. All isolates, in our study were found to be imipenem and meropenem sensitive.…”
Section: Methodsmentioning
confidence: 99%
“…Location is another important factor to consider in association with changes in body image. 68,69 The prevision of outcomes is another element that needs to be considered, trying to determine the characteristics of patients' lives after discharge. Some validated scales can be helpful.…”
Section: Main Findings Of the Studymentioning
confidence: 99%
“…a tulle dressing). However dressing changes often result in pain and reinjury of the tissue, increased length of the re-epithelialization process and may require anesthetization of the patient [ 24 , 25 ].…”
Section: Reviewmentioning
confidence: 99%